Hubungan Derajat Nyeri Dismenore Dengan Aktivitas Akademik Dan Ekstrakurikuler Siswi SMAN 9 Maros Tahun Akademik 2023/2024 - Arif, Andi Tasya Nurul Fadhilah; Abrar, Hanan Khasyrawi; Murnita, Ika Azdah (Bosowa Medical Journal, 2024)
Dysmenorrhea is defined as pain during menstruation. This pain often appears as lower abdominal cramps that occur throughout menstruation. This disorder is classified into two forms, namely primary dysmenorrhea and secondary dysmenorrhea. Primary dysmenorrhea is pain during menstruation without any anatomical abnormalities of the genitals, while secondary dysmenorrhea is menstrual pain associated with clear anatomical abnormalities. The purpose of this study was to determine the relationship between academic and extracurricular activities of SMAN 9 Maros students in the 2023/2024 academic year. The research method used in this study was a cross-sectional approach using primary data from the questionnaire of Dysmenorrhea sufferers. The results of the study that have been conducted regarding the relationship between the degree of dysmenorrhea pain with academic and extracurricular activities of SMAN 9 Maros students in the 2023/2024 academic year with a total of 164 samples based on the questionnaires collected showed that there was a significant relationship between academic and extracurricular activities with the degree of dysmenorrhea pain. From the data, there are female students who are at risk in academic and extracurricular activities tend to have moderate and severe dysmenorrhea pain. On the other hand, female students who are not at risk in academic and extracurricular activities show a lower degree of pain, namely a mild degree